The Implementation of Learning Curriculum of Traditional Islamic Boarding School Darul Huda in the Era of Society 5.0 - Erham As’ari; Ahmad Zainuri; Yuniar; Tasurun Amma (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
The objectives of this study were to analyze the concept of learning curriculum and to implement learning curriculum in Darul Darul Huda Kajang traditional Islamic boarding school by focusing on the basic principle of Islamic scientific values that are being the foundation of Islamic boarding school. The study used a qualitative approach of case study type. Furthermore, the object of the study was the curriculum of Darul Darul Huda Kajang traditional Islamic boarding school. The data collection techniques used observation, interviews and analysis of literature documents. Moreover, the informants were determined based on the hierarchy of Islamic boarding school structure. The results of the study showed that the main learning objective was to build student’s pious character, Islamic knowledge mastery, and knowledge implementation in daily life. Continuously, the learning materials focused on yellow books and several references books including journals, digital books, and learning methods involving sorogan method, bandongan, demonstration method/worship practice, deliberation method of bahtsul masa’il and muhafazhah or memorization method. Then, the assessment emphasized on qualitative aspects such as the ability to understand and explain Islamic teachings and their application in daily life. This research has significant relevance in facing the changing paradigm of education in the digital era. Along with the emergence of the Society 5.0 era, Islamic boarding schools must not only be the guardians of scientific traditions but also be pioneers in combining tradition with technology. The implication of the results of this study is the importance of the openness of boarding schools to new things that become demands and the need for resources that are able to face the times but still preserve the values of local wisdom and traditional boarding school culture.